Live food for the early larval growth of catfish Heteropneustes fossilis (Bloch) - Nayak, P K; Mishra, J; Kumar, K; Sahoo, S; Satpathy, B B; Ayyappan, S (Indian Journal of Fisheries, 2011)
Zooplankton, Artemia, snail meat, fish meat and rice bran used as feed were tested as diets in the early larval growth of H. fossilis over a twelve-day period. Among all the food types, zooplankton was found to produce the best growth results followed by Artemia, while other food types yielded poor results.